THE GENUS TETRACERA (DILLENIACEAE) IN THE EASTERN OLD WORLD - HOOGLAND, R. D. (REINWARDTIA, 1953)
1. An account of the genus Tetracera L. in the eastern Old World (Asia, Malaysia,Australia, New Caledonia) is given. The Malaysian species have already been in cluded in the revision of the Dilleniaceae in "Flora malesiana" (I 4: 141-149. 1951). 2. The main part of the present paper consists of a key to the species, followed by a systematic treatment of the 15 species admitted for the region. 3. Latin diagnoses are given for three new subspecies under Tetracera asiatiea (Lour.) Hoogl. and two new varieties under Tetracera nordtiana F. Muell. 4. A number of species are reduced either to the rank of variety or to synonymy. 5. Distribution-maps are provided for the species of which a relatively large number of specimens has been studied.